The nexus between regional eco-environmental degradation and rural impoverishment in China - Zhou, Yang; Li, Yurui; Liu, Yansui (Habitat international, 2020)
Regional environmental degradation and impoverishment interact and restrict each other. While acknowledging this relationship, little is known about the extent of their impact. By integrating multi-source data, this study used econometric models and spatial analysis techniques to explore the geographical distribution pattern of rural poverty in China, identify the key factors affecting rural improvement and quantitatively reveal the relationship between regional eco-environmental degradation and improvement. The results show that complex geographical environment, fragile ecological environment, frequent natural disasters, endemic diseases prevalent and the aging of social subjects do affect and even aggravate rural impoverishment in China. Terrain relief degree was identified as a determinative factor of rural poverty in China, and the rural poverty rate increases by 0.3–0.45% for every 1-m increase in terrain fluctuation. Further analysis showed that distribution of poverty-stricken population in rural China overlaps spatially with areas with fragile ecology, high incidence of geological disasters, poor geographical environment and aging population. The impact of eco-environmental degradation on poverty depends on the types of eco-environmental problems faced by the poor. The types of poverty-stricken areas in rural China can be divided into five categories: disaster-driven, endemic disease-driven, eco-environment degradation-driven, ecological protection restricted and grain-producing restricted. Poverty alleviation, disaster risk prevention, disease reduction and ecological environmental protection need to be promoted in collaboration. Differentiated and targeted anti-poverty measures for different types of poverty are urgently needed. •The nexus between regional eco-environmental degradation and impoverishment are investigated.•Poverty occurs naturally and geographically.•Complex geo-environment leads to regional poverty, and other unfavorable factors aggravate it.•China's rural poverty can be divided into five main geographical types.